Techno-economic assessment for viability of some waste as cooling pads in evaporative cooling system - Ndukwu, Macmanus C; Manuwa, Seth I (International Journal of Agricultural and Biological Engineering, 2015)
The viability of some waste as cooling pads for evaporative cooling application in South-Western Nigeria was experimentally assessed. This is to ascertain their effectiveness as a substitute for costly imported pads in a low income environment. Also presented was the feasibility of utilizing standalone evaporative coolers for storage and selling of fruits in South-Western Nigeria. Natural ambient air was forced through the various pads at three different fan speeds and constant cooling pad thickness of 30 mm. Performance characteristics were considered based on daily analysis using temperature and humidity data measured from morning to evening at location co-ordinates latitude 7°10′N and longitude 5°05′E for 6 weeks. The daily temperature T and humidity h ranged between 26°C≤T≤45°C and 28% ≤ h2 ≤ 80%. Temperature difference ΔT and humidity difference Δh of 0.6°C≤ ΔT ≤ 18.3ºC and 1.0% ≤ Δh ≤ 53% was achieved for the four cooling pad materials tested at three fan speeds. Highest ΔT and Δh was recorded at fan speed of 4 m/s with shredded latex foam and jute sack respectively. The cooling efficiency (η) calculated for all the pads under the three speeds ranged from 17.3% ≤ η ≤98.8%. Payback period (PBP) analysis indicated the considered EVC is economically feasible and investors will break even in 1.75 years. Keywords: evaporative cooling, agricultural residues, passive cooling, cooling effectiveness, cooling pads DOI: 10.3965/j.ijabe.20150802.952